Prescribing and using vitiligo treatments: lessons from a nested process evaluation within the HI‐Light vitiligo randomized controlled trial. (30th May 2022) - Leighton, Paul; Chalmers, Joanne R.; Batchelor, Jonathan M.; Rogers, Andy; Akram, Perways; Haines, Rachel H.; Meakin, Garry D.; White, Jennifer; Ravenscroft, Jane C.; Sach, Tracey H.; Santer, Miriam; Whitton, Maxine E.; et al.
Abstract: Background: The HI‐Light Trial demonstrated that for active, limited vitiligo, combination treatment with potent topical corticosteroid (TCS) and handheld narrowband ultraviolet B offers a better treatment response than potent TCS alone. However, it is unclear how to implement these findings. Aim: We sought to answer three questions: (i) Can combination treatment be used safely and effectively by people with vitiligo?; (ii) Should combination treatment be made available as routine clinical care?; and (iii) Can combination treatment be integrated within current healthcare provision? Methods: This was a mixed‐methods process evaluation, including semi‐structured interviews with a purposive sample of trial participants, structured interviews with commissioners, and an online survey and focus groups with trial staff. Transcripts were coded by framework analysis, with thematic development by multiple researchers. Results: Participants found individual treatments easy to use, but the combination treatment was complicated and required nurse support. Both participants and site investigators felt that combination treatment should be made available, although commissioners were less certain. There was support for the development of services offering combination treatment, although this might not be prioritized above treatment for other conditions. A 'mixed economy' model was suggested, involving patients purchasing their own devices, although concerns regarding the safe use of treatments mean that training, monitoring and ongoing support are essential. The need for medical physics support may mean that a regional service is more practical. Conclusion: Combination treatment should be made available for people seeking treatment for vitiligo, but services require partnership with medical physics and ongoing training and support for patients. Abstract : The HI‐Light Vitiligo Trial showed that hand‐held home‐based narrowband ultraviolet B phototherapy (NB‐UVB) in combination with potent topical corticosteroid (TCS) gives a better treatment response than potent TCS alone in people with active, limited vitiligo. Trial participants and healthcare professionals agreed that combination treatment with home‐based, hand‐held NB‐UVB and potent TCS should be made available to people with active, limited vitiligo. Some participants found it complicated to follow a regimen of combination treatment with TCS and hand‐held NB‐UVB. It was not always possible to predict which people were more likely to have difficulties. Concerns regarding the safe use of TCS and NB‐UVB mean that careful selection of suitable recipients for combination treatment, followed by adequate training, monitoring and ongoing support, are essential. Medical physics services need to be closely involved in the provision of home‐based hand‐held NB‐UVB treatment, to ensure that devices are properly checked and maintained. This may mean that regional, rather than local, provision is more practical